INTERNET OF THINGS ERA: IMPLEMENTATION OF PAI LEARNING BASED ON IMTAK AND SCIENCE AND TECHNOLOGY INTEGRATION IN SCHOOLS - Ja'far Shidiq, Ahmad; Mujahidin, Endin (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The basic education level is the initial foundation for forming Imtak and developing science and technology. If the formation of Imtak and the development of science and technology fail to be carried out at the stage of basic education age, it will certainly give birth to students who are not academically qualified, characteristic, and spiritualistic. This study aims to describe the implementation of PAI learning based on the integration of Imtak and Science and Technology at Mts Hidayatussalikin Pangkalpinang. The method used is a qualitative method with a case study type. Research data collection techniques are obtained through interviews, observations, and documentation studies. The results of this study revealed three findings, namely: (1) the conceptual level carried out by school elements in learning based on the integration of Imtak and Science and Technology, (2) the operational level in the formation of Imtak and the development of science and technology students, and 3) the architectural level that supports learning in schools. Based on the results of this research, it is expected to provide alternative and innovative solutions for teachers in learning based on the integration of Imtak and Science and Technology in schools.